Beat the heat Singapore : improving fire preparedness amongst homeowners in Singapore - Chuah, Jacinta Pei Yun (Nanyang Technological University, 2020)
Beat the Heat Singapore is a risk communication campaign that aims to promote the adoption of fire extinguishers amongst household owners aged 35 to 49, who have at least one child, and do not own a fire extinguisher – our post-campaign analysis revealed a significant 23.3% increase of fire extinguisher ownership amongst our target audience. Guided by the Protection Motivation Theory, Beat The Heat Singapore is the first local campaign to tackle fire safety with the innovative use of Virtual Reality technology and adopt the angle of positive child-based messaging to raise household fire preparedness. Qualitative semi-structured interviews and quantitative pretest-posttest control group design research conducted informed our campaign that the public has a low sense of response cost and response efficacy. Thus, we want to empower parents to believe that they can provide a safe environment for their children with a fire extinguisher that is an affordable and comprehensive fire fighting tool in contrast to common household items. We disseminated these key messages to our target audience mainly via paid advertisements on Facebook and delivered our Virtual Reality game to the public through both digital and offline efforts. This paper will detail the campaign process and will provide implications and recommendations for policy and practice.